The Effectiveness of Antiviral Treatments for Patients with HBeAg-Positive Chronic Hepatitis B: A Bayesian Network Analysis - Zhang Hao; Zhu Biqing; Yang Ling; Zeng Wenting (Canadian Journal of Gastroenterology and Hepatology)
This network analysis is to determine the most effective treatment in HBeAg-positive patients. PubMed databases were searched for randomized controlled trials. Bayesian network meta-analysis was used to calculate the pairwise hazard ratios, 95% credible intervals, and ranking of surrogate outcomes. 9 studies were identified. The results show that NA add-on PEG IFN might be a better antiviral approach for HBeAg-positive patients in end point of treatment, with a comparable results of nucleoside/nucleotide analogs (NA), PEG IFN, PEG IFN add-on NA, PEG IFN combined NA, and PEG IFN combined placebo in alanine aminotransferase (ALT) normalization and HBV DNA undetectable. Cumulative probabilities of being the most efficacious treatment were NA add-on PEG IFN (30%) for HBeAg loss. The second efficacious (23%) is HBeAg seroconversion. This network analysis shows that NA add-on PEG IFN might be a better antiviral approach for HBeAg-positive patients in end point of treatment. But the long-term efficiency should be further determined.